UPAYA PENINGKATAN KINERJA SATUAN SAMAPTA DALAM PELAKSANAAN PATROLI GUNA MENINGKATKAN PUBLIC TRUST DI WILAYAH HUKUM POLRES SEMARANG - ALIVIQO PANDU VIRGANTARA (Advances in Police Science Research Journal, 2022)
ABSTRACT IMPROVEMENT EFFORT OF SAMAPTA UNIT PERFORMANCE IN THE IMPLEMENTATION OF PATROL TO INCREASE PUBLIC TRUST IN THE JURISDICTION OF SEMARANG POLICE RESORT ALIVIQO PANDU VIRGANTARA, NO. AK. 18.075, aliviqo@gmail.com The global problems that often occur in Indonesia revolve around crime. The role of the Samapta Unit in handling crime in Indonesia is needed in carrying out preventive actions for crime. Polri expects public trust in the Police because this is an indicator of the success of the Police as a protector, protector, and public servant. Economic conditions in the Semarang Police Area decreased so that the crime rate during the pandemic increased dramatically. The Samapta Unit of the Semarang Police Also has a routine patrol program that aims to prevent and overcome criminal acts in the Semarang Police Jurisdiction, so that public trust has increased. This research aims to find out how to improve the performance of samapta units in the implementation of patrols and find out what efforts are being made to improve public trust in the jurisdiction of the Semarang Police. The methods used in this study are in the form of interviews of related parties in the Semarang Police And questionnaires given to the people of the Semarang Police jurisdiction. The results of this study aim to increase public confidence in the Semarang Regency Area by reviewing the performance of patrol members of the Samapta Unit of the Semarang Police. Overall, the performance of patrol members has been good, however, there are still mistakes from patrol members. It is hoped that this paper can improve the performance of patrol members which has an impact on increasing public trust in the Semarang Police Jurisdiction.